2012
DOI: 10.4037/ajcc2012999
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Albumin on Diuretic Response to Furosemide in Patients With Hypoalbuminemia

Abstract: A closed-book, multiple-choice examination following this article tests your under standing of the following objectives:1. Examine the effect of albumin on the diuretic effect of furosemide. 2. Correlate findings of various studies related to the sequential administration of albumin and furosemide. 3. Identify study limitations and opportunities for future research related to administration of furosemide and albumin.To read this article and take the test online, visit www.ajcconline.org and click "CNE Articles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 11 publications
0
26
0
1
Order By: Relevance
“…Some studies have suggested that the concurrent use of albumin may increase furosemide-induced diuresis in hypooncotic patients with acute respiratory distress syndrome/acute lung injury [65,66] and cirrhosis-induced ascites [67], although not in all critically ill patients [68]; whether this strategy has any effect on patient-centered clinical outcomes is unclear.…”
Section: Some Backgroundmentioning
confidence: 99%
“…Some studies have suggested that the concurrent use of albumin may increase furosemide-induced diuresis in hypooncotic patients with acute respiratory distress syndrome/acute lung injury [65,66] and cirrhosis-induced ascites [67], although not in all critically ill patients [68]; whether this strategy has any effect on patient-centered clinical outcomes is unclear.…”
Section: Some Backgroundmentioning
confidence: 99%
“…41 Small studies have shown that coadministration of albumin with diuretics in refractory diuretic-resistant edema confers modest clinical benefit, a finding that warrants confirmation with large, prospective studies. 42 The first step in the evaluation of patients with hypoproteinemia is to exclude other common causes like malnutrition or liver and renal disease. The most commonly used and reliable method to determine enteric protein loss is to determine the clearance of α-1 antitrypsin (A1AT) from plasma.…”
Section: Protein-losing Enteropathymentioning
confidence: 99%
“…that thorough analysis is required before using human albumin in a direct association and as the firstchoice treatment. 7,24,34 The possible positive impact within clinical practice from using a combination of human albumin and furosemide among patients with edema is not associated with correction of hypovolemia. There is agreement that one possible explanation for the Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…17 Some studies have shown that human albumin enhances the effect of diuretics, 13,[18][19][20][21] while other studies have failed to show any difference in the results from comparisons between ways of using diuretics: on a stand-alone basis or in association with albumin. 17,[22][23][24][25] Some other studies have contraindicated this combination of human albumin and diuretics for treating edema in NS, 26 while yet others have shown benefit from stand-alone use of albumin.…”
mentioning
confidence: 99%